Current state of the stock market Indices in the world (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The study aims to show the current state of the stock indices in the world. It is a descriptive study. The results indicate that 94 countries selected, are built 3.429 rates, classified in main, additional, sectoral and other. There is a wide variety of characteristics that identify the stock index. The estimated model tells us that the number of companies on the main index is determined by new productive investment from enterprises and the issuance of more securities to the market.
Keywords: stock; stock exchange values; index; market capital